El principio de complementariedad y las estrategias de actuación de la Corte Penal Internacional en la fase de examen preliminar: ¿Por qué la Corte Penal Internacional mantiene su examen preliminar, pero no abre una investigación, sobre la situación en Colombia? - Héctor Olásolo Alonso (Revista Electrónica de Estudios Internacionales, 2012)
The article analyses the role of the Prosecutor’s Office in applying the complementarity principle through its preliminary examinations during the first ten years of the International Criminal Court. It underlies the important role that the ICC has started playing within the International Community, the need for a different strategy for each of the situations under analysis by the ICC Office of the Prosecutor, and the significant role of the preliminary examinations to strengthen national courts and rule of law in the states concerned